Advantages and disadvantages of bioplastics production from starch and lignocellulosic components - Abe, Mateus Manabu [UNESP] (2021)
The accumulation of plastic wastes in different environments has become a topic of major concern over the past decades; therefore, technologies and strategies aimed at mitigating the environmental impacts of petroleum products have gained worldwide relevance. In this scenario, the production of bioplastics mainly from polysaccharides such as starch is a growing strategy and a field of intense research. The use of plasticizers, the preparation of blends, and the reinforcement of bioplastics with lignocellulosic components have shown promising and environmentally safe alternatives for overcoming the limitations of bioplastics, mainly due to the availability, biodegradability, and biocompatibility of such resources. This review addresses the production of bioplastics composed of polysaccharides from plant biomass and its advantages and disadvantages.